Justification of the choice intraligamentary anesthesia in outpatient dental practice (LLC "Endo Press", 2020)
The efficacy and safety of use intraligamentary anesthesia in the treatment of caries and its complications single-rooted and multi-rooted teeth using 4% articaine with epinephrine 1:100 000, 1:200 000 and without a vasoconstrictor. Effectiveness of anesthesia was assessed using objective methods elektroodontometrii and registration of microcirculation dental pulp. Security is controlled by monitoring indices of Central hemodynamics.